Research handbook on strategic communication - Falkheimer, Jesper; Heide, Mats (Cheltenham : Edward Elgar Publishing, 2022)
"Strategic communication as a research field and a professional practice is becoming increasingly relevant for organizations. Bringing together contributions from almost 60 leading international scholars, this dynamic Research Handbook on Strategic Communication is a timely contribution to a vivid and developing academic field. Divided into three key parts - fundamentals, perspectives, and processes - the Research Handbook provides a holistic overview of target-oriented communication in and between organizations and society. The Research Handbook begins by addressing core issues in the discipline, introducing theories of communication, strategy, propaganda, and the public sphere. Chapters further explore strategic communication from a range of institutional, democratic, spatial, gendered, professional, and technological perspectives. The final section covers an extensive array of strategic communication processes, from corporate branding, communication management, and public diplomacy to corporate social responsibility, political communication, and social media. Offering an advanced overview of relevant theories, concepts, and methods in strategic communication, this comprehensive Research Handbook will be an essential resource for graduate students and scholars of communication studies, sociology, social psychology, organizational theory, marketing, and public relations. Practitioners will benefit from its combination of theoretical and practical insights."--From back cover.
Includes bibliographical references and index.
Keywords: Communication in management; Strategic planning